On the problems and prospects of native flora conservation in culture: from the experience of Samara University Botanical Garden - S. A. Rozno; I. V. Ruzayeva; T. M. Zhavkina; A. V. Pomogaybin; L. M. Kavelenova; O.A. Kuzovenko (Проблемы ботаники Южной Сибири и Монголии, 2020)
The information on the experience of preserving rare natural flora species ex situ is presented in the article.The largest amount of research conducted relates to herbaceous plants. For Juniperus sabina L., an extremely raregymnosperm plant of the Samara region, numerous clumps have been formed in the Botanical Garden, including somefrom local origin material. There is experience of successful reintroduction of both grassy and woody species (juniper).